The Effects of Rilmenidine and Perindopril on Arousal Blood Pressure during 24 Hour Recordings in SHR - Lim, Kyungjoon (PLoS One, 2016)
The surge in arterial pressure during arousal in the waking period is thought to be largely due to activation of the sympathetic nervous system. In this study we compared in SHR the effects of chronic administration of the centrally acting sympatholytic agent rilmenidine with an angiotensin converting enzyme inhibitor perindopril on the rate of rise and power of the surge in mean arterial pressure (MAP) that occurs with arousal associated with the onset of night. Recordings were made using radiotelemetry in 17 adult SHR before and after treatment with rilmenidine (2mg/kg/day), perindopril (1mg/kg/day) or vehicle in the drinking water for 2 weeks. Rilmenidine reduced MAP by 7.2 ± 1.7mmHg while perindopril reduced MAP by 19 ± 3mmHg. Double logistic curve fit analysis showed that the rate and power of increase in systolic pressure during the transition from light to dark was reduced by 50% and 65%, respectively, but had no effect on diastolic pressure. Rilmenidine also reduced blood pressure variability in the autonomic frequency in the active period as assessed by spectral analysis which is consistent with reduction in sympathetic nervous system activity. Perindopril had no effect on the rate or power of the arousal surge in either systolic or diastolic pressure. These results suggest that the arousal induced surge in blood pressure can largely be reduced by an antihypertensive agent that inhibits the sympathetic nervous system and that angiotensin converting enzyme inhibition, while effective in reducing blood pressure, does not alter the rate or power of the surge associated with arousal.